Assimilatory potential of helicoverpa armigera reared on host (chickpea) and nonhost (cassia tora) diets - Dawkar, Vishal V.; Chikate, Yojana R.; Gupta, Vidya S.; Slade, Susan E.; Giri, Ashok P. (Journal of Proteome Research, 2011)
Adaptation to plant allelochemicals is a crucial aspect of herbivore chemical ecology. To understand an insect ecology, we studied an effect of nonhost Cassia tora seed-based diet (Ct) on growth, development, and molecular responses in Helicoverpa armigera. We employed a comparative approach to investigate the proteomic differences in gut, hemolymph, and frass of H. armigera reared on a normal (chickpea seed-based, Cp) and Ct diet. In this study, a total of 46 proteins were identified by nano-LC-MS(E). Among them, 17 proteins were up-regulated and 29 proteins were down-regulated when larvae were exposed to the Ct diet. Database searches combined with GO analysis revealed that gut proteases engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification were down-regulated in the Ct fed larvae. Proteins identified in H. armigera hemolymph were found to be involved in defense mechanisms. Moreover, proteins found in frass of the Ct fed larvae were observed to participate in energy metabolism. Biochemical and quantitative real-time PCR analysis of selected candidate proteins showed differential gene expression patterns and corroborated with the proteomic data. Our results suggest that the Ct diet could alter expression of proteins related to digestion, absorption of nutrients, adaptation, defense mechanisms, and energy metabolism in H. armigera.
Keywords: adaptation; Cassia tora; Gene expression; Helicoverpa armigera; proteomics

Amylase gene expression patterns in Helicoverpa armigera upon feeding on a range of host plants - Kotkar, Hemlata M.; Bhide, Amey J.; Gupta, Vidya S.; Giri, Ashok P. (Gene, 2012)
Expression of two amylase genes (HaAmy1 and HaAmy2) was studied in Helicoverpa armigera (Hubner; Lepidoptera: Noctuidae) feeding on different host plants and during larval development. Alignment of HaAmy1 and HaAmy2 with other insect amylases shows similarities with known Lepidopteran amylase transcripts. H. armigera amylase gene expression is influenced by the availability of reducing sugars, sucrose and starch content of host plants and further correlates to the pool of reducing sugars in the gut and haemolymph of larvae. HaAmy1 and HaAmy2 during larval development on two host plants viz., maize (cereal) and marigold (ornamental) showed their relative difference. Results support the view that when host plants differ in their macronutrients, relationships of enzymes and substrates are flexible. The present work highlights the distribution of HaAmy1 and HaAmy2 (i) during various stages of insect development (second, fourth and sixth instar, pupa, adult and egg), (ii) in various tissues viz., head, haemolymph, fat body, integument and whole larval body of H. armigera feeding on artificial diet and (iii) in three gut regions of larvae fed on various diets. Complexity in expression of amylase genes suggests existence of mechanisms involved to detect nutrient balance required for avoiding fitness costs and focus their importance in insect nutrition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Diets; Digestive amylase; Gene expression; Helicoverpa armigera; Nutrition

Alterations in the helicoverpa armigera midgut digestive physiology after ingestion of pigeon pea inducible leucine aminopeptidase - Lomate, Purushottam R.; Jadhav, Bhakti R.; Giri, Ashok P.; Hivrale, Vandana K. (Plos One, 2013)
Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on the diets supplemented with pigeon pea LAP. Aminopeptidase activities in larvae remain unaltered in presence or absence of inducible LAP in the diet. On the contrary, serine proteinase activities were significantly decreased in the larvae reared on pigeon pea LAP containing diet as compared to larvae fed on diet without LAP. Our data suggest that pigeon pea inducible LAP is responsible for the degradation of midgut serine proteinases upon ingestion. Reduction in the aminopeptidase activity with LpNA in the H. armigera larvae was compensated with an induction of aminopeptidase activity with ApNA. Our findings could be helpful to further dissect the roles of plant inducible LAPs in the direct plant defense against herbivory.

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Antiviral drugs prioritization for COVID-19 management based on rational selection - Joshi, Rakesh S.; Giri, Ashok P.; Kulkarni, Mahesh J.; Gupta, Mahesh; Verma, Savita; Chaudhry, Dhruva; Deshmukh, Narendra; Chugh, Anita (Current Science, 2021)
The SARS-CoV-2 infection has resulted in COVID-19 pandemic worldwide. It has infected around 0.1 billion individuals and caused 2 million fatalities across the globe till mid-January 2021. Drug repurposing has been utilized as the most preferred therapeutic intervention for COVID-19 mitigation due to its necessity and feasibility. To prioritize therapeutic regime against COVID-19, we used 61 antiviral drugs and their combinations. Selected molecules were subjected to virtual screening against: (i) human angiotensin-converting enzyme 2 receptor binding domain (hACE-2) which serves as an anchor for virus attachment and entry, (ii) SARS-CoV-2 RNA dependent RNA polymerase (RdRp) responsible for viral RNA replication, and (iii) SARS-CoV-2 main protease (M-Pro) needed for viral polyprotein slab proteolytic processing. Based on docking score, pharmacodynamic and pharmacokinetic parameters, combinations of Daclatasvir, Elbasvir, Indinavir, Ledipasvir, Paritaprevir and Rilpivirine were analysed further. Our analysis suggested Sofosbuvir in combination with Ledipasvir and Daclatasvir as potential therapeutic agents for SARS-CoV-2. The combined score suggests that these combinations have superior anti-SARS-CoV-2 potential than Remdesivir and other investigational drugs. The present work provides a rationale-based approach to select drugs with possible anti-SARS-CoV-2 activity for further clinical evaluation.
Keywords: Drug repurposing; hACE-2; main protease; RNA dependent RNA polymerase; SARS-CoV-2

Auxin: an emerging regulator of tuber and storage root development - Kondhare, Kirtikumar R.; Patil, Aruna B.; Giri, Ashok P. (Plant Science, 2021)
Many tuber and storage root crops owing to their high nutritional values offer high potential to overcome food security issues. The lack of information regarding molecular mechanisms that govern belowground storage organ development (except a tuber crop, potato) has limited the application of biotechnological strategies for improving storage crop yield. Phytohormones like gibberellin and cytokinin are known to play a crucial role in governing potato tuber development. Another phytohormone, auxin has been shown to induce tuber initiation and growth, and its crosstalk with gibberellin and strigolactone in a belowground modified stem (stolon) contributes to the overall potato tuber yield. In this review, we describe the crucial role of auxin biology in development of potato tubers. Considering the emerging reports from commercially important storage root crops (sweet potato, cassava, carrot, sugar beet and radish), we propose the function of auxin and related gene regulatory network in storage root development. The pattern of auxin content of stolon during various stages of potato tuber formation appears to be consistent with its level in various developmental stages of storage roots. We have also put-forward the potential of three-way interaction between auxin, strigolactone and mycorrhizal fungi in tuber and storage root development. Overall, we propose that auxin gene regulatory network and its crosstalk with other phytohormones in stolons/roots could govern belowground tuber and storage root development.
Keywords: Auxin; Potato; Storage root; Sweet potato; Tuber

Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites

Adsorption based downstream processing approach for penicillin V from a Penicillium chrysogenum BIONCL I22 culture filtrate - Mishal, Bela H.; Das, Sancharini; Mahajan, Vaishnavi N.; Dharne, Mahesh S.; Joshi, Rakesh S.; Giri, Ashok P. (ACS Omega, 2024)
Penicillin V (phenoxy methyl penicillin) is highly sought after among natural penicillins because of its exceptional acid stability and effectiveness against common skin and respiratory infections. Given its wide-ranging therapeutic uses, there is a need to establish a greener method for its maximum recovery to reduce the carbon footprint. Here, we have identified and validated optimized operational conditions for resin-based penicillin V recovery. It was observed that Amberlite XAD4 had the highest penicillin V hydrophobic adsorption capacity among the other screened resins. Kinetic and isothermal studies using linear and nonlinear regression analysis showed that the adsorption process well fitted with pseudo-second-order kinetics (R-2 = 0.9816) and the Freundlich adsorption isotherm model (R-2 = 0.9871). Adsorption equilibrium was attained within 4 h, while maximum adsorption was observed at 3 mg/mL penicillin V concentration. Furthermore, the optimized extraction protocol was compared with the conventional butyl acetate-based downstream processing. Under optimum conditions resin-based penicillin V recovery was 2-fold higher as compared to the solvent extraction method and the resin could be reused for over six cycles without compromising the yield. These findings signify substantial progress toward the development of an environmentally sustainable approach for penicillin V recovery and a potentially viable method for extractive fermentation.

Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Kallure, Gopal S.; Sahoo, Shubhranshu Shekhar; Kale, Rutuja S.; Barvkar, Vitthal T.; Kontham, Ravindar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2024)
One of the most prevalent bioactive molecules present in the oral secretion (OS) of lepidopteran insects is fatty acid amino acid conjugates (FACs). Insect dietary components have influence on the synthesis and retaining the pool of FACs in the OS. We noted differential and diet-specific accumulation of FACs in the OS of Helicoverpa armigera by using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Interestingly, we identified FACs hydrolyzing enzyme aminoacylase (HaACY) in the OS of H. armigera through proteomic analysis. Next, we have cloned, expressed, and purified active recombinant HaACY in the bacterial system. Recombinant HaACY hydrolyzes all the six identified FACs in the OS of H. armigera larvae fed on host and non-host plants and releases respective fatty acid and glutamine. In these six FACs, fatty acid moieties vary while amino acid glutamine was common. Glutamine obtained upon hydrolysis of FACs by HaACY might serve as an amino acid pool for insect growth and development. To understand the substrate choices of HaACY, we chemically synthesized, purified, and characterized all the six FACs. Interestingly, rHaACY also shows hydrolysis of synthetic FACs into respective fatty acid and glutamine. Our results underline the importance of diet on accumulation of FACs and role of aminoacylase(s) in regulating the level of FACs and glutamine.
Keywords: Aminoacylase; Fatty acid amino acid conjugates; Glutamine; Helicoverpa armigera; Oral secretion

Aroma Alchemy: uridine diphosphate-dependent glycosyltransferases mediated regulation of fruit aroma and flavor biosynthesis - Vare, Tejas B.; Joshi, Rakesh S.; Giri, Ashok P. (Phytochemistry Reviews, 2024)
The aroma compounds contribute to fruits flavor, taste, and nutritional value. These compounds include various chemical classes such as terpenoids, lactones, ketones, esters, acids, alcohols, and their derivatives. Uridine diphosphate-dependent glycosyltransferases (UGTs) modify these compounds by covalently adding one or multiple sugar molecules. This glycosylation process converts volatile, unstable, and hydrophobic aroma compounds into hydrophilic, stable, and slow-releasing reservoirs of fruit flavor. The diversity and spatio-temporal expression patterns of UGTs play a crucial role in forming a wide range of glycosylated aroma compounds. This review focuses on aroma-related compounds in both free and glycosylated-bound forms found in commercial vital fruits. We discuss various fruit-specific UGTs and their role in the glycosylation of aroma compounds. Based on structural and functional information on UGTs, we have assessed sugar donor specificity and the residues responsible for the same. Moreover, phylogenetic analysis of characterized UGTs provides insights into their substrate preferences. We also surveyed the expression dynamics of UGTs during fruit ripening, as the switching between aglycon and glycosylated-bound forms of aroma compounds significantly impacts fruit quality. Potential applications of UGTs in the food and fragrance industry have been discussed. The information reviewed could be beneficial for developing novel methods for flavor manipulation of commercially important glycosides derived from natural resources.
Keywords: Aroma; Flavor; Fruit; Glycoconjugates; Glycosyltransferase; Volatile compounds

Article chitinase inhibition induces transcriptional dysregulation altering ecdysteroid-mediated control of spodoptera frugiperda development - Barbole, Ranjit S.; Sharma, Shivani; Patil, Yogita; Giri, Ashok P.; Joshi, Rakesh S. (Iscience, 2024)
Chitinases and ecdysteroid hormones are vital for insect development. Crosstalk between chitin and ecdysteroid metabolism regulation is enigmatic. Here, we examined chitinase inhibition effect on Spodopsilencing and overexpression resulted in ecdysone receptor deregulation. Transcription factors, like Neverland, and other ecdysteroid biosynthesis genes might lead to their upregulation in berberine-fed chitinase activity's impact on ecdysone biosynthesis and its transcriptional crosstalk.